Ethnographies of educational and cultural conflicts strategies and resolutions - Jeffrey, Bob, 1946-; Walford, Geoffrey (Amsterdam ; Boston : Elsevier JAI, 2004)
National Curricula need to be interpreted in terms of the cultures and experience of learners and adjusted accordingly, for example a literacy and history curriculum needs to include perspectives relevant to the local culture. Teachers, learners, families and communities mediate, appropriate, subvert, and challenge the processes of policy implementation, curriculum engagement and pedagogic practices to make educational experiences more meaningful. These articles exemplify the conflicts, the coping strategies and resolutions adopted by those at the policy implementation interface. Examination of these processes using ethnographic methods identifies and characterises these tensions and provides research findings that can be used to construct lasting solutions that are commensurate with complex situations. The writers in this volume have carried out ethnographies that illuminate educational disjunctions, ambiguities and tensions, agency, strategic action and resolution. Their methodology enables them to show, in detail, how incongruencies arise, how contexts affect interactions, what kind of agency operates, and the circumstances leading to resolutions. Six articles focus on educational inequality, three on identity development and we include three that discuss methodological issues of partisanship in researching equality issues.
The case for partisan research: Erving Goffman and researching social inequalities / S.H. Hillyard -- Should ethnographers be against inequality?: on Becker, value neutrality, and researcher partisanship / Martyn Hammersley -- ICT and educational (dis)advantage: cultural resources and the digital divide / Lawrence Angus, Wendy Sutherland-Smith and Ilana Snyder -- Writing inequalities: literacy and social class in three primary schools / Ann WIlliams and Eve Gregory -- Addressing inequities: lessons in syncretism from Mexican American and Puerto Rican children at home and at school / Susi Long and Dinah Volk -- "I don't think she knew I couldn't do it": Bangladeshi pupils and achievement in the early years of schooling / Sue Walters -- Making it: Caribbean children transgressing barriers and inequality to achieve success / Colton Paul -- Naming and dealing with inequality: immigrants students' perspective of unequal spaces in the classroom / Ruth Silva -- Identity formation of female students in a predominantly female, multiethnic high school / Kathleen Gewinner -- The risk zone: intersections of identity and literacy in a multiage, multilingual classroom / Katie van Sluys -- Reducing inequalities in field relations: who gets the power? / Caroline Hudson.
Includes bibliographical references.
Description based on print version record.
Keywords: Educational anthropology; Educational equalization; Ethnology; Physical anthropology & ethnography; Education -- Research